Pengalaman Psikologis Ibu Merawat Anak dengan Retardasi Mentaldi SLB Negeri Rokan Hulu Riau: Pengalaman Psikologis Ibu Merawat Anak Dengan Retardasi Mental di SLB Negeri Rokan Hulu Riau - Nia Aprilla; Marjohan Marjohan; Basmanelly basmanelly (Jurnal Kesehatan Komunitas, 2019)
Amount 59,26% mothers with mental retardation childrens are faced several problems in caring of their children. The aim of this study was find out the psychological mother experiences in caring for their children with mental retardation in a special needs school at Rokan Hulu Regency, Riau Province. This was qualitative research with phenomenology approach. The phenomena ini this study was the psychological mother experiences in caring their children with mental retardation. This research was conducted from 12 May until 11 June 2017. And the number of informants we interviewed were 5 mothers. Informants were mothers who're having the children with mental retardation who send their children to special need schools at Rokan Hulu Regency Riau Province. Informants were chosen by purposive sampling technique. The data were collected by home visit the informants for 30-60 minutes in 2-3 times with in-depth interview The data were analyzed by applying the Colaizzi technique. The results showed that 6 themes were identified in this study:(1) the mother's initial response when known their children having mental retardation; (2) the attitude of parents in caring for their children; (3) sibling rivalry; (4) the burden when caring children with mental retardation; (5) the efforts to get health services and (6) mother's expectations. The nurses are expected to facilitate in created a peer groups of mothers who have children with mental retardation as a community to share the experiences in caring for children, including supporting group, self-help group, and cognitive behavior therapy.